2014
DOI: 10.1017/s0007123413000562
|View full text |Cite
|
Sign up to set email alerts
|

Candidate Ethnicity and Vote Choice in Britain

Abstract: This article develops and tests a set of theoretical mechanisms by which candidate ethnicity may have affected the party vote choice of both white British and ethnic minority voters in the 2010 British general election. Ethnic minority candidates suffered an average electoral penalty of about 4 per cent of the three-party vote from whites, mostly because those with anti-immigrant feelings were less willing to vote for Muslims. Ethnic minority voter responses to candidate ethnicity differed by ethnic group. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
84
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(97 citation statements)
references
References 61 publications
6
84
0
2
Order By: Relevance
“…First, we do not find any evidence to suggest that the effect of Muslim candidature on Muslim voters depends upon the ethnic composition of the constituency. Unlike Carsey (1995) or Avery and Fine (2012), though in line with Fisher et al (2014) we found no tendency for the effect of minority candidature to depend on the ethnic composition of the constituency, nor for the Muslim candidate effect to be stronger where there is a greater proportion of Muslims. Similarly we do not find any evidence that the effect of Muslim candidature on Hindus varies by ethnic composition.…”
Section: The Impact Of Candidate Religion On Voting Behavioursupporting
confidence: 66%
See 2 more Smart Citations
“…First, we do not find any evidence to suggest that the effect of Muslim candidature on Muslim voters depends upon the ethnic composition of the constituency. Unlike Carsey (1995) or Avery and Fine (2012), though in line with Fisher et al (2014) we found no tendency for the effect of minority candidature to depend on the ethnic composition of the constituency, nor for the Muslim candidate effect to be stronger where there is a greater proportion of Muslims. Similarly we do not find any evidence that the effect of Muslim candidature on Hindus varies by ethnic composition.…”
Section: The Impact Of Candidate Religion On Voting Behavioursupporting
confidence: 66%
“…To measure the political incentives that may moderate the influence of candidate religion on voting behaviour we compute each party's Distance from Contention (for third and lower placed parties this is the difference between the 2012 share of the vote for the party and that for the second placed party, and 0 if the party came first or second in the constituency). This serves as a proxy for the local strength of the different parties, and distinguishes between those parties which voters might reasonably expect to have a realistic chance of winning (those which come first or second) and those parties which are less competitive (see also Fisher et al, 2014). 2 Candidates who come third or lower may therefore be strategically abandoned and considered irrelevant.…”
Section: Datamentioning
confidence: 99%
See 1 more Smart Citation
“…However, in the case above, ethnicity or immigrant status appears to hamper it. The impact of ethnicity on voting decision has been documented in research (Vermeersch 2011;Bergh and Bjorklund, 2011;Stegmaier, Lewis-Beck, and Smets 2013;Fisher et al 2015). Key findings indicate that visible minorities are more likely to vote for members of their own ethnic or racial group than otherwise, especially when they are victims of structural discrimination.…”
Section: Case Of African Immigrants In Finland At the Municipal Levelmentioning
confidence: 99%
“…28 Stegmaier, Lewis-Beck, and Smets 2013, 283. 29 Fisher et al 2014. ballot paper. 30 In the context of this article, however, this lack of prior information is of no concern.…”
mentioning
confidence: 99%